2003
DOI: 10.1016/s0304-3959(02)00382-2
|View full text |Cite
|
Sign up to set email alerts
|

‘CatWalk’ automated quantitative gait analysis as a novel method to assess mechanical allodynia in the rat; a comparison with von Frey testing

Abstract: A characteristic symptom of neuropathic pain is mechanical allodynia. In animal models of neuropathic pain, mechanical allodynia is often assessed using von Frey filaments. Although the forces applied with these filaments are highly reproducible, there are various disadvantages of using this method. Testing paradigms and definitions of withdrawal threshold are not standardised. Moreover, measurements may be influenced by various conditions, such as ambient temperature, humidity, weight bearing of the limb and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
224
4
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(246 citation statements)
references
References 28 publications
14
224
4
4
Order By: Relevance
“…49 Accordingly, we did not find mechanical allodynia or thermal hyperalgesia in rats with SCI, and we assessed that PROG did not induce such behaviors either, neither measured by classical tests, such as hot and cold plate and the Hargreaves method, nor with CatWalk parameters normally decreased in animals in which allodynia is developing (Stance, Print Intensity, Print and Max area). 50,51 Data obtained in the present study demonstrate that PROG improved locomotor outcome after thoracic contusion. There is no general consensus about the functional effects of PROG after SCI, however.…”
Section: Prog Reduced Secondary Injury and White Matter Pathologysupporting
confidence: 56%
See 1 more Smart Citation
“…49 Accordingly, we did not find mechanical allodynia or thermal hyperalgesia in rats with SCI, and we assessed that PROG did not induce such behaviors either, neither measured by classical tests, such as hot and cold plate and the Hargreaves method, nor with CatWalk parameters normally decreased in animals in which allodynia is developing (Stance, Print Intensity, Print and Max area). 50,51 Data obtained in the present study demonstrate that PROG improved locomotor outcome after thoracic contusion. There is no general consensus about the functional effects of PROG after SCI, however.…”
Section: Prog Reduced Secondary Injury and White Matter Pathologysupporting
confidence: 56%
“…Decreases in those parameters have been previously related to mechanical allodynia. 50,51 Thermal sensitivity. As for mechanical stimulation, no statistically significant differences were observed between groups, showing that our model did not produce thermal hyperalgesia and that PROG administration did not induce changes in the nociceptive behavior (Fig.…”
Section: Sensory Functionmentioning
confidence: 99%
“…In particular, maximum contact area and stance phase duration of the ischemic limb were reduced, and swing phase duration of the ischemic limb was increased, while stride length of the ischemic limb did not alter in our model. Vrinten and colleagues showed that paw placement‐related parameters of the injured limb such as contact area and contact intensity were reduced in their chronic constriction injury model, a neuropathic pain model 24. Their model also showed prolongation of swing phase duration and shortening of stance phase duration in the injured limb 24.…”
Section: Discussionmentioning
confidence: 99%
“…Vrinten and colleagues showed that paw placement‐related parameters of the injured limb such as contact area and contact intensity were reduced in their chronic constriction injury model, a neuropathic pain model 24. Their model also showed prolongation of swing phase duration and shortening of stance phase duration in the injured limb 24. Parvathy and colleagues evaluated gait disturbances in an inflammatory pain model 25.…”
Section: Discussionmentioning
confidence: 99%
“…A number of methods were developed to measure pain in small animals, including measurement of weight-bearing (Vrinten, 2003), mechanical sensitivity (Fernihough, 2004), vocalization (Han, 2005) and gait analysis such as footprint analysis (Marxen, 2004) and motion analysis [Coulthard, 2002;Coulthard, 2003;Varejao 2002]. As chronic tendinopathy is characterized with activity-related pain, it is more plausible to Page 5 of 37 A c c e p t e d M a n u s c r i p t 4 detect the pain-associated changes in dynamic state (walking) instead of static state (standing).…”
Section: Introductionmentioning
confidence: 99%